Buletin Peternakan : KUALITAS FISIK TELUR ASIN ITIK PEGAGAN YANG DIPROSES DENGAN MENGGUNAKAN ABU PELAPAH KELAPA SAWIT DAN ASAP CAIR - fitra yosi (Peternakan UGM, 2016)
Liquid smoke is a useful material for use in the process of preserving eggs. The purpose of this study was to determine the effect of the use of palm oil fronds ash and liquid smoke in the process of salting to the physical quality of pegagan duck’s egg. This study was assingned in a Completely Randomized Design, which consists of 5 treatments and 4 replications.